Relationship of skeletal muscle mass, length of sports experience, and sexual maturity with bone density and geometry in adolescent athletes - Bim, Mateus Augusto; de Lima, Tiago Rodrigues; Martins, Rafael; Miranda, Clair Costa; Fernandes, Rômulo Araújo [UNESP]; Pelegrini, Andreia (Elsevier, 2025)
Objective: To identify the relationship between length of sports experience, muscle mass, and sexual maturity with bone mineral density (BMD) and geometry in adolescent basketball and track and field athletes. Method: The study included adolescent (11–18 years) athletes, of both sexes, who practiced basketball (n = 26) or track and field (n = 24). Skeletal muscle mass was measured by bioelectrical impedance analysis. Data on sports training and sexual maturity were collected through a questionnaire. Total body, lumbar, femoral, and forearm BMD were determined by dual-energy X-ray absorptiometry. Femoral scans were used to generate bone geometry measurements (femur strength index, cross-sectional area, cross-sectional moment of inertia, section modulus, and buckling ratio). Bone outcomes were compared between modalities by the Mann–Whitney U-test or Student's t-test and by analysis of covariance with adjustment for sports experience, sexual maturity, and skeletal muscle mass. Results: In the crude analysis, the basketball group had higher mean values for height, body weight, muscle mass, femoral neck BMD, cross-sectional area, and cross-sectional moment of inertia. In the covariate-adjusted analysis, the track and field group had higher total-body-less-head (0.995 vs. 1.035, p = 0.043), lumbar (1.012 vs. 1.107, p = 0.005), and radial (0.734 vs. 0.800, p = 0.005) BMD. Muscle mass was the main covariate influencing bone parameters, followed by sexual maturity. Conclusion: Skeletal muscle mass was the main determinant of bone outcomes in adolescent athletes, followed by sexual maturity, underscoring the importance of considering these variables when assessing bone health in this population.
Keywords: Adolescents; Athletes; Bone mineral density; Muscle mass; Sexual development